Knowledge Advancement and Application in E-business for SME’s in Nigeria: An Epilogue (A Case of Delta State) - Omede, Nduka Kenneth; Ejeh, Patrick (Management Analysis Journal, 2020)
SMEs continuously seeking for knowledge advancement to improve their performance and keep pace with the new ways of doing business, the acquisition of knowledge equip SMEs to come to terms with the realities of the new order. This study examined knowledge advancement and application in e-business for SMEs in Nigeria. To achieve these laudable objectives two hypotheses were formulated to establish whether or not there is a relationship existing between the two intervening variables i.e. knowledge advancement and application in e-business and the growth and development for SMEs in Nigeria in general and Delta state in particular. Survey research design was adopted, while data were obtained from structured questionnaire and analyzed using Pearson’s product-moment coefficient of correlation. From the analysis, the results indicated that there is an existing relationship between the variables. Based on the findings it was concluded that for SMEs to stand the test of time, the need to continue to seek for new ways of doing business and innovation becomes imperative. Among others, the study recommended that SMEs should embark on intensive training, skill acquisition and development exercise to keep pace with the new order.